PENERAPAN TERAPI SENTUHAN UNTUK MENGATASI HIPERTERMI PADA ANAK DENGAN DENGUE HAEMORAGIC FEVER (DHF) DI RUANG ANGGREK RS BHAKTI WIRA TAMTAMA SEMARANG - Khusna, Nurul; Hastuti, Witri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Dengue Hemorrhagic Fever (DHF) is a contagious infection caused by the dengue virus and is transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes which can trigger fever or hyperthermia. Dengue Haemorrhagic Fever (DHF) is still a global public health problem, especially in tropical and subtropical regions, including Indonesia, one of the dengue endemic countries. The dengue mortality rate in Central Java has increased from 2018 to 2021. The data in 2021 reached 2.7 percent. Objective: to describe the application of touch therapy to treat hyperthermia in children by providing touch therapy to reduce the body temperature of children with Dengue Haemorrhagic Fever (DHF). ). Method: using a descriptive method by describing nursing care for DHF children in the Anggrek room of RST Bhakti Wira Tamtama Semarang, using pre-test and post-test. The research was conducted on 11 – 13 December 2023. Results: After the Touch Therapy intervention was carried out, the results showed a decrease in body temperature in DHF children. Conclusion: Touch Therapy can treat hyperthermia in children with DHF. Suggestion: It is hoped that Touch Therapy can be used as an independent nursing intervention in reducing children's body temperature in DHF patients.